Do cryptic species matter in macroecology? Sequencing European groundwater crustaceans yields smaller ranges but does not challenge biodiversity determinants. Issue 2 (13th April 2017) - Eme, David; Zagmajster, Maja; Delić, Teo; Fišer, Cene; Flot, Jean‐François; Konecny‐Dupré, Lara; Pálsson, Snæbjörn; Stoch, Fabio; Zakšek, Valerija; Douady, Christophe J.; Malard, Florian
Abstract : Ecologists increasingly rely on molecular delimitation methods (MMs) to identify species boundaries, thereby potentially increasing the number of putative species because of the presence of morphologically cryptic species. It has been argued that cryptic species could challenge our understanding of what determine large‐scale biodiversity patterns which have traditionally been documented from morphology alone. Here, we used morphology and three MMs to derive four different sets of putative species among the European groundwater crustaceans. Then, we used regression models to compare the relative importance of spatial heterogeneity, productivity and historical climates, in shaping species richness and range size patterns across sets of putative species. We tested three predictions. First, MMs would yield many more putative species than morphology because groundwater is a constraining environment allowing little morphological changes. Second, for species richness, MMs would increase the importance of spatial heterogeneity because cryptic species are more likely along physical barriers separating ecologically similar regions than along resource gradients promoting ecologically‐based divergent selection. Third, for range size, MMs would increase the importance of historical climates because of reduced and asymmetrical fragmentation of large morphological species ranges at northern latitudes. MMs yielded twice more putative species than morphology and decreased by 10‐fold the average species range size. Yet, MMs strengthened the mid‐latitude ridge of high species richness and the Rapoport effect of increasing range size at higher latitudes. Species richness predictors did not vary between morphology and MMs but the latter increased the proportion of variance in range size explained by historical climates. These findings demonstrate that our knowledge of groundwater biodiversity determinants is robust to overlooked cryptic species because the latter are homogeneously distributed along environmental gradients. Yet, our findings call for incorporating multiple species delimitation methods into the analysis of large‐scale biodiversity patterns across a range of taxa and ecosystems.